The Effect of Rainfall on the Reduction of Hotspot in Indonesia 1n 2019-2020 - Bambang Hero Saharjo; Dimas Adi Nugraha (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Forest and land fires (Karhutla) are a phenomenon that often occurs in Indonesia every year. Moreover, there are many changes in land use, such as on the islands of Sumatra and Kalimantan. For example, in Jambi, South Sumatra, West Kalimantan and Central Kalimantan. Climatic factors can affect the occurrence of forest and land fires. The purpose of this study was to determine the relationship between hotspots and rainfall on the occurrence of forest and land fires in Indonesia 2019 to 2020. This study used NASA MODIS hotspot data, administrative maps, and rainfall data from the BMKG. The results of this study indicate that rainfall is very influential on the number of hotspots, if the rainfall is low then the hotspots is high and vice versa. July to November is the dry season in 2019, while 2020 is from August to October. From the results of the P-Value correlation test, only South Kalimantan Province is below the 0.05 limit, which is 0.041. Meanwhile, from the results of the R-Person correlation test, Jambi Province has a positive notation (+). Which means that rainfall has no effect on the number of hotspots in the two provinces. Keywords: correlation, fire, hotspot, modis, precipitation